1989
DOI: 10.3109/00365528909092231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bicarbonate, Acetate, and Citrate on Water and Sodium Movement in Normal and Cholera Toxin-Treated Rat Small Intestine

Abstract: Bicarbonate, citrate, or acetate are commonly included in oral rehydration solutions to correct acidosis and possibly because of their ability to promote water and sodium absorption. We have investigated the effect of these anions on water and sodium transport in normal and also in secreting (cholera toxin-treated) rat small intestine using a single-pass perfusion technique. In normal jejunum bicarbonate and acetate produced net absorption, and citrate net secretion of both water and sodium. In normal ileum al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…In the cecum this effect was minimal (6.7 versus 5.3 ml). The strongest effect of CT was observed in the first 15 min of the experiment, suggesting that the removal of CT from the mucosa diminished its effect on intestinal secretion and supporting previous evidence that CT does not bind firmly to intestinal epithelial cells (1)(2)(3)(4)(5)8).…”
supporting
confidence: 83%
“…In the cecum this effect was minimal (6.7 versus 5.3 ml). The strongest effect of CT was observed in the first 15 min of the experiment, suggesting that the removal of CT from the mucosa diminished its effect on intestinal secretion and supporting previous evidence that CT does not bind firmly to intestinal epithelial cells (1)(2)(3)(4)(5)8).…”
supporting
confidence: 83%
“…This is of interest as we have previously shown that acetate stimulates sodium absorption in the normal small intestine but not in the secreting small intestine after exposure to cholera toxin. 12 In this paper we report our studies of acetate absorption in rat jejunum using in vivo steadystate perfusion. The concentration dependence of total acetate absorption, its relationship to luminal pH and total CO2 and its inhibition by propionate and a structurally unrelated buffer were studied in the jejunum.…”
mentioning
confidence: 99%
“…Another factor that can affect absorption of bioactive molecules is viscosity induced by food additives, such as guar gum [33]. Citrate, an approved food additive, is also known to increase viscosity in the presence of collagen and fibrous material [34] as well as change the water absorption profile in different parts of the small intestine [35]. It has been added to different oral rehydration formulations to modulate acidosis and glycemic index as a viscosity-promoting agent [3638].…”
Section: Discussionmentioning
confidence: 99%